Pharmaceutical Composition of Cefazolin Sodium Coupled Silver Nanoparticles Dermal Gel with Improved Antibacterial Activity - Kumar, Amit; Singh, Sukhdev (International Journal of Psychosocial Rehabilitation, 2019)
In present invention, a novel gel was designed for enhancing the antibacterial activity of cefazolin sodium by using the nanoparticles synthesized by green chemistry approach against S. aureus, E.coli and methicilin resistant Staphylococcus aureus infected wounds and to provide faster healing of infected wounds. Skin damage is one of the most common lesions that people suffer from, and some injuries such as chronic wounds and deep burns are notoriously difficult to eliminate. The already existing therapies have been proved to be inadequate and unsatisfactory. An imminent global public health problem is the rapid development of antibiotic resistance to pathogeic microbes. Nanoparticles are the small-sized particles that exist on a nanometer scale. Modern nanotechnology offers an unprecedented ability to revolutionize and invent new medicines or treatments or to increase the efficacy of current treatments. Dermal gel or hydrogel is a promising anti-bacterial product. Dermal gel or hydrogel is a biomaterial synthesized with a water-soluble natural polymer, or a synthesized polymer, which transforms into gel by alteration of signals such as temperature, ionic force, pH, ultraviolet exposure, etc. Dermal gels is one of the ideal biomaterial for the supply of drugs in antimicrobial areas due to its high hydrophilicity, its special three-dimensional network, fine biocompatibility and cell adherence.